Mechanochemical synthesis and thermal decomposition of Mg(AlH4)(2) - Kim, Yoonyoung; Lee, Eung-Kyu; Shim, Jae-Hyeok; Cho, Young Whan; Yoon, Kyung Byung (ELSEVIER SCIENCE SA, 2006)
Magnesium alanate Mg(AlH4)(2) has been synthesized by mechanochemically activated metathesis reaction between NaAlH4 and MgCl2 without solvent, this metathesis reaction proceeded completely. The thermal decomposition behavior of solvent-free Mg(AlH4)(2) has been analyzed by TG/MS and DSC. It has been confirmed that Mg(AlH4)(2) decomposes in two steps: the first decomposition reaction Mg(AlH4)(2) -> MgH2 + 2Al + 3H(2) is exothermic and starts at about 115 degrees C. The second one MgH2 + 2Al -> 1/2Al(3)Mg(2) + 1/2Al + H-2 is endothermic in total and starts at about 240 degrees C, although the formation reaction of Al3Mg2 (3Al + 2Mg -> Al3Mg2) is exothermic. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: ALUMINUM HYDRIDES; MAGNESIUM ALANATE; X-RAY; ACTIVATION; LITHIUM